The Connection Between Testicular Cancer, Minority Males, and Planned Parenthood. Issue 5 (September 2018) - Adams, Wesley B.; Rovito, Michael J.; Craycraft, Mike
Testicular cancer (TCa) is the most prevalent neoplasm diagnosed in males aged 15–40 years. Lack of access to care is a key impediment to early-stage TCa diagnosis. Health equity concerns arise, however, as poor access largely manifests within underserved male populations, therefore, placing them at a higher risk to develop late-stage TCa. Planned Parenthood Federation of America (PPFA) offers a myriad of male reproductive/sexual health care options, including TCa screening and referral services. Therefore, expanding these amenities in traditionally underserved communities may address the concern of TCa screening opportunities. An ecological analysis was performed using data from the United States Cancer Statistics, American Community Survey, and PPFA databases to assess the impact of TCa upon minority males, identify associations between PPFA services and minority males, and provide future implications on the role PPFA may play in bridging health-care access gaps pertaining to TCa screenings. Results indicate that states with higher rates of poverty and uninsured individuals, as well as specifically Black/African American males, have lower TCa incidence and limited access to screening services. PPFA service presence and Black/African American, as well as uninsured, males had a negative association but revealed positive correlations with TCa incidence. Considering the emerging TCa outcome disparities among minority males, expanding PPFA men's health services is crucial in providing affordable options to help identify testicular abnormalities that are early stage or carcinoma in situ. Many at-risk males have limited means to obtain TCa screening services. Expanding this discussion could provide a foundation for future advocacy.